Effect of inorganic and organo-mineral fertilizers on the uptake of selected heavy metals by Helianthus annuus L. and Tithonia diversifolia (Hemsl.) under greenhouse conditions - Adewolea, M.B.; Adeoyeb, G.O.; Sridharc, M.K.C. (Taylor & Francis, 2023)
,Toxicological & Environmental